Neutral network learning algorithms for microarray classification - Shwe, Sin Aung. (2008)
In this thesis, we focus on two supervised machine learning algorithms in cancer classification, namely the Backpropagation algorithm (BP) and Extreme Learning Machine algorithm (ELM). The objective of this project is to determine the best generalization network for BP and ELM for microarray data analysis for three problems, namely "ALL-AML" Leukemia, Colon Tumor and Primate Splice Junction's gene sequence.